2012
DOI: 10.1210/en.2012-1069
|View full text |Cite
|
Sign up to set email alerts
|

Intestinotrophic Glucagon-Like Peptide-2 (GLP-2) Activates Intestinal Gene Expression and Growth Factor-Dependent Pathways Independent of the Vasoactive Intestinal Peptide Gene in Mice

Abstract: The enteroendocrine and enteric nervous systems convey signals through an overlapping network of regulatory peptides that act either as circulating hormones or as localized neurotransmitters within the gastrointestinal tract. Because recent studies invoke an important role for vasoactive intestinal peptide (VIP) as a downstream mediator of glucagon-like peptide-2 (GLP-2) action in the gut, we examined the importance of the VIP-GLP-2 interaction through analysis of Vip(-/-) mice. Unexpectedly, we detected abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 43 publications
(55 reference statements)
2
21
1
Order By: Relevance
“…Treatment with GLP-2 increased the abundance of and activated VIP-expressing neurons in healthy and inflamed rat colon through a PI3Kg/Akt-mediated pathway [67][68][69]. Noticeably, GLP-2's proliferative effects on the intestinal crypts and small intestinal mucosa do not require VIP [70]. In addition to reducing inflammation, GLP-2 exhibits antioxidant activity, reduces inflammation-induced oxidative stress in intestinal tissues [71], and provides protection from gut ischemia and reperfusion injury [72]; although the mechanisms of these actions have not been fully investigated to date.…”
Section: Physiological Effects Of Glp-2 On Intestinal Tissuesmentioning
confidence: 96%
“…Treatment with GLP-2 increased the abundance of and activated VIP-expressing neurons in healthy and inflamed rat colon through a PI3Kg/Akt-mediated pathway [67][68][69]. Noticeably, GLP-2's proliferative effects on the intestinal crypts and small intestinal mucosa do not require VIP [70]. In addition to reducing inflammation, GLP-2 exhibits antioxidant activity, reduces inflammation-induced oxidative stress in intestinal tissues [71], and provides protection from gut ischemia and reperfusion injury [72]; although the mechanisms of these actions have not been fully investigated to date.…”
Section: Physiological Effects Of Glp-2 On Intestinal Tissuesmentioning
confidence: 96%
“…Interestingly, GLP2 is also known to increase disaccharide absorption by increasing the expression and activity of SGLT1 (Cheeseman, 1997;Cheeseman and Tsang, 1996). In addition, GLP2R activation enhanced KGF production (Yusta et al, 2012). Whether the increase of KGF expression in the SuperEGF group is via the up-regulation of GLP2 by EGF is to be further explored.…”
Section: Egfmentioning
confidence: 99%
“…For example, we have demonstrated that mice deficient in VIP (VIP KO) exhibit ameliorated responses to experimental autoimmune encephalomyelitis (EAE) and to lipopolysaccharide (LPS)-induced endotoxemia [33,34]. In addition, VIP KO mice displayed a milder weight loss and intestinal damage than WT mice in a dextran sodium sulphate (DSS) murine model of disease [35]. These reports hint that long term lack of VIP is somehow protective in the development of this disease or that VIP is necessary for the development of certain inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%